Comparison of cardiac output and cardiac index values measured by critical care echocardiography with the values measured by pulse index continuous cardiac output (PiCCO) in the pediatric intensive care unit:a preliminary study - Nagehan Aslan; Dincer Yildizdas; Ozden Ozgur Horoz; Yasemin Coban; Fadli Demir; Sevcan Erdem; Yasar Sertdemir (BMC, 2020)
Abstract Background Planning optimal fluid and inotrope-vasopressor-inodilator therapy is essential in critically ill children. Pulse index Contour Cardiac Output (PiCCO) monitoring is an invasive, hemodynamic monitor that provides parameter measurements such as cardiac output (CO), cardiac index (CI). Use of ultrasonography and critical care echocardiography by the pediatric intensivists has increased in recent years. In the hands of an experienced pediatric intensivist, critical echocardiography can accurately measure both CO and CI. Our objective in this study is to compare the CO and CI values measured by pediatric intensivist using critical care echocardiography to the values measured by PiCCO monitor in critically ill pediatric patients. Methods A prospective observational study from a tertiary university hospital PICU. A total of 15 patients who required advanced hemodynamic monitoring and applied PiCCO monitoring were included the study. The diagnosis of patients were septic shock, cardiogenic shock, acute respiratory distress syndrome, pulmonary edema. Forty nine echocardiographic measurements were performed and from 15 patients. All echocardiographic measurements were performed by a pediatric intensive care fellow experienced in cardiac ultrasound. The distance of left ventricle outflow tract (LVOT) in the parasternal long axis and LVOT-Velocity Time Integral (LVOT-VTI) measurement was performed in the apical five chamber image. Cardiac output_echocardiography (CO_echo) and CI_echocardiography (CI_echo) were calculated using these two measurements. PiCCO (PiCCO, Pulsion Medical Systems, Munich, Germany) monitoring was performed. Cardiac output (CO_picco) and CI (CI_picco) were simultaneously measured by PiCCO monitor and echocardiography. We performed a correlation analysis with this 49 echocardiographic measurements and PiCCO measurements. Results We detected a strong positive correlation between CO_echo and CO_picco measurements (p < 0.001, r = 0.985) and a strong positive correlation between CI_echo and CI_picco measurements (p < 0.001, r = 0.943). Conclusions Our study results suggest that critical care echocardiography measurement of CO and CI performed by an experienced pediatric intensivist are comparable to PiCCO measurements. The critical care echocardiography measurement can be used to guide fluid and vasoactive-inotropic management of critically ill pediatric patients.